Musa Dah i bliżej. Zaczynając od powieści Franza Werfla. - Roszak, Joanna (Slavia Occidentalis, 2015)
The subject of the first part of the article is an interpretation of Franz Werfel’s novel Forty days of Musa Dah, published in 1933 and containing in its the name of the place where five thousand Armenians made a stand against the Turks in September and October 1915. The book made the author a national hero of the Armenians. However, this Jewish writer simultaneously sensed the approaching Shoah. Hence, in the second part of the paper, I show how the novel grew in importance during World War II: Musa Dah was compared to the resistance in the Jewish ghettos (e.g. the situation of the population in Bialystok). Janusz Korczak was to discuss the novel in the summer of 1941, also the chronicler of the Warsaw Ghetto, Emmanuel Ringelblum, in June 25, 1942 compared the Warsaw Ghetto to Musa Dah.